2015
DOI: 10.1111/ppa.12360
|View full text |Cite
|
Sign up to set email alerts
|

The β‐amylase genes: negative regulators of disease resistance for Verticillium dahliae

Abstract: Little is known about the role of plant primary metabolism in defence against pathogens. The present study is the first investigation published that examines the role of b-amylase (BAM) genes upon fungal, Verticillium dahliae, infection. The responses of Arabidopsis thaliana plants impaired in BAM1, BAM2, BAM3, BAM4 genes, along with double, triple and quadruple mutants of those genes, were used to explore the involvement of BAM in the host plant-V. dahliae interaction. Less severe symptoms were recorded in ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…Gkizi et al . () have assigned a negative role for BAM genes in the partial resistance of A. thaliana plants against V. dahliae . Our results indicated that ‘Picual’ plants showed an overall induction of BAM unigenes upon infection with V. dahliae D pathotype, in contrast to ‘Frantoio’ plants in which their global expression remained unaltered.…”
Section: Discussionmentioning
confidence: 99%
“…Gkizi et al . () have assigned a negative role for BAM genes in the partial resistance of A. thaliana plants against V. dahliae . Our results indicated that ‘Picual’ plants showed an overall induction of BAM unigenes upon infection with V. dahliae D pathotype, in contrast to ‘Frantoio’ plants in which their global expression remained unaltered.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, genes coding for β-amylases were also found in both libraries. These enzymes have been recently proposed as negative regulators in Arabidopsis partial resistance against V. dahliae (Gkizi et al, 2015 ). The role of detected olive elongation factors and β-amylases in the interaction olive- V. dahliae remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…FRAEX38873_v2_000086110 is a Leucine-rich repeat receptor-like serine/threonine-protein kinase β-amylase (BAM) 3, which is involved in fungal resistance in Arabidopsis 40 . Gene…”
Section: Fraex38873_v2_000296810 Matches An Ankyrin Repeat-containingmentioning
confidence: 99%